2019
DOI: 10.1002/mbo3.937
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of curcumin on dual‐species biofilms formed by Streptococcus mutans and Candida albicans

Abstract: Streptococcus mutans and Candida albicans are often isolated from plaques associated with early childhood caries. However, there are limited studies examining how these microorganisms interact with one another and how best to manage them. Recent studies have shown that curcumin (CUR), a natural compound, has the potential to independently control both of these microorganisms. The purpose of this study was to investigate how S. mutans and C. albicans respond in mono‐ and dual‐species biofilms challenged with CU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 35 publications
0
42
0
1
Order By: Relevance
“…In turn, Alalwan et al [ 48 ] observed its anti-adhesive effects against C. albicans biofilm formation at the sub-inhibitory concentration of MIC/2. The antibiofilm properties of curcumin have also been reported for various bacterial species, including A. baumannii [ 42 ], E. faecalis [ 39 ], E. coli , P. aeruginosa , P. mirabilis , S. marcescens [ 24 ], S. epidermidis [ 49 ], and S. mutans [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Alalwan et al [ 48 ] observed its anti-adhesive effects against C. albicans biofilm formation at the sub-inhibitory concentration of MIC/2. The antibiofilm properties of curcumin have also been reported for various bacterial species, including A. baumannii [ 42 ], E. faecalis [ 39 ], E. coli , P. aeruginosa , P. mirabilis , S. marcescens [ 24 ], S. epidermidis [ 49 ], and S. mutans [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting samples were mounted on aluminum cylinders containing carbon strips and evaporated under high vacuum (Denton Vacuum Desk V; Jeol Ltd., Moorestown, NJ, United States) for gold coating. The topographical characteristics of the biofilms were analyzed by electron microscopy (JSM-6610 Series Scanning Electron Microscope; Jeol Ltd., United States) at the School of Dentistry of UNESP at Araraquara, SP, Brazil (Martinez et al, 2010;Costa-Orlandi et al, 2014;Li et al, 2019).…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The inhibitory effects of chelerythrine on the biofilm formation were observed by field emission scanning electron microscopy (FESEM; Nova Nano SEM-450, FEI, Hillsboro, OR, USA) and confocal laser scanning microscopy (CLSM; Zeiss LSM 880 with Airyscan), as described previously [21]. Approximately 1 × 10 6 CFU/mL of mono-species and dual-species were cultured on the glass coverslips in individual wells of a 24-well microtiter plate, and treated with chelerythrine at 0, 1/8, 1/4, and 1/2 MIC at 37 • C for 24 h. For FESEM analysis, followed by treatment, the glass coverslips with biofilms were kept in sterile water containing 2.5% glutaraldehyde (v/v; Sigma-Aldrich, USA) at −4 • C for 2 h. Then, biofilms were rinsed three times with 10 mM PBS (pH 7.0) and dehydrated in water-alcohol solutions at C T E D various alcohol concentrations of 30%, 50%, 70%, 90%, and 100% for 10 min each.…”
Section: Biofilm Inhibition Assaymentioning
confidence: 99%